2022
DOI: 10.22541/au.166004672.28025918/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symbiont-specific responses to environmental cues in a threesome lichen symbiosis

Abstract: Photosymbiodemes are a special case of lichen symbiosis where one lichenized fungus engages in symbiosis with two different photosynthetic partners, a cyanobacterium and a green alga, to develop two distinctly looking photomorphs. We investigated differential gene expression in photosymbiodemes of the lichen Peltigera britannica at different temperatures representing mild and putatively stressful conditions and compared gene expression of thallus sectors containing cyanobacterial photobionts with thallus secto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…This symbiotic strategy generates two distinct photomorphs with either cyanobacteria or green alga as primary photobionts. A recent study on the lichen Peltigera britannica explored how gene expression in the fungus varied between thallus sectors with only cyanobacterial photobionts, and those with green algal photobionts (where photobionts are hosted as auxiliary partners only in small, separated organs called cephalodia), particularly under different temperature conditions (Almer et al, 2022). Results of RNA-sequencing showed photobiont-mediated differences in fungal gene expression.…”
Section: Forummentioning
confidence: 99%
See 1 more Smart Citation
“…This symbiotic strategy generates two distinct photomorphs with either cyanobacteria or green alga as primary photobionts. A recent study on the lichen Peltigera britannica explored how gene expression in the fungus varied between thallus sectors with only cyanobacterial photobionts, and those with green algal photobionts (where photobionts are hosted as auxiliary partners only in small, separated organs called cephalodia), particularly under different temperature conditions (Almer et al, 2022). Results of RNA-sequencing showed photobiont-mediated differences in fungal gene expression.…”
Section: Forummentioning
confidence: 99%
“…Genes associated with distinct biological processes are upregulated in association with specific symbionts, indicating that the type of symbiotic partner has a significant influence on the fungal gene expression. When examining the effects of temperature, Almer et al (2022) found that higher temperatures caused an increase in gene expression related to heat shock response across all involved organisms. Both types of photobionts showed increased expression of photosynthesis-related genes at 15°C and 25°C.…”
Section: Forummentioning
confidence: 99%